Weaponization of Social Media Resulting in Unrest in the Society (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The fast growth in social media use has led to a shift in social discourse, political communications, and civic incorporation. Nevertheless, the manipulative aspect of it as a political instrument has caused the weaponization against people through platforms like digital media, which has also been a significant cause of social instability. The paper will focus on the role of algorithmic amplification, misinformation, coordinated disinformation campaigns, and echo chambers in enhancing polarization and fuelling real-life instability. It examines the causality of the connection between propaganda online and offline outcomes, which involve communal strains, protest escalation, mob violence, and institutional warning loss. It applies a doctrinal and analytical methodology to measure structural weaknesses in social media systems and constraints of current regulatory methods. The article posits that the unregulated digital manipulation endangers social unity and democracy. It concludes that dealing with weapons of social media necessitates enhanced digital literacy, open platform management, proportional regulation, and multi-televangel stakeholder cooperation to ensure that digital narratives are not reflected in the unrest of society without infringing on the freedom of expression.